The Validity of Agreements Made Without Authority: A Juridical Study on the Principle of Legitimacy in Civil Law - Suhendi, Muhammad Pradikta; Astutik, Sri; Widodo, Ernu (International Journal on Advanced Science, Education, and Religion, 2025)
This article explores the legal consequences of agreements entered into by individuals or entities lacking proper legal authority to act on behalf of another party. Within the framework of Indonesian civil law, especially as outlined in the Kitab Undang-Undang Hukum Perdata (Civil Code), the validity of such agreements is subject to strict requirements concerning consent, authority, and legal competence. The study highlights the distinction between void and voidable contracts, emphasizing the legal implications of agreements made ultra vires or without representation. By examining doctrinal legal principles and relevant case studies, this paper demonstrates how the absence of authority affects the binding power of a contract, and under what conditions a third party may be held liable. The analysis also touches upon the principle of good faith, apparent authority, and ratification as possible legal remedies. This research contributes to a clearer understanding of the boundaries of legal representation and the protection of contractual rights in civil transactions.